Burkholderia phymatum Strains Capable of Nodulating Phaseolus vulgaris Are Present in Moroccan Soils - Talbi, C. (American Society for Microbiology (ASM), 2010)
Phylogenetic analysis of 16S rRNA, nodC, and nifH genes of four bacterial strains isolated from root nodules of Phaseolus vulgaris grown in Morocco soils were identified as Burkholderia phymatum. All four strains formed N(2)-fixing nodules on P. vulgaris and Mimosa, Acacia, and Prosopis species and reduced acetylene to ethylene when cultured ex planta.